Biological Activity of a Growth Factor for Ovarian Cells - Jones, Kenneth L. (1974)
The biological activity of a protein growth factor is described. This factor was isolated from bovine pituitary tissue, and its activity was tested on cells of rat ovarian origin. Activity was assayed as growth-promoting potential measured by cell counts and is concentrationdependent. Similar growth stimulation was not produced by several cyclic nucleotides tested, neither was there crossreactivity between this growth factor and a chemically similar one produced by rat liver cells.